Effect of different music tempos on aerobic performance and recovery - Köse, Bereket; Atli, Ahmet (Progress in Nutrition, 2019)
The aim of this study was to determine effect of different music tempos on aerobic performance and recovery period. Thirty-five healthy male students (age=22.63±2.94, body mass=71.40±10.71, height=178.24±9.95) who were studying at Faculty of Sport Sciences voluntarily participated in this study. Participants carried out Bruce treadmill test with 72 hour intervals under three conditions: slow tempo music (100 bpm), fast tempo music (140 bpm) and no music. Anova was applied for statistical analysis. Fast tempo music (18.28±3.01 minute) was determined to improve running time by 4.63% and 3.10% compared to no music (17.47±2.83 min) and slow tempo music (17.73±3.09 min), respectively (p0.05). Lactate accumulation during 15 min recovery was found lower with slow tempo music compared to fast tempo and no music conditions (p